Arterial Hypertension and Kidney Circulation - Beaufils, M. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2006)
Hypertension may cause renal vascular lesions and glomerular damage, constituting hypertensive nephrosclerosis. This ultimately may lead to end-stage renal failure, mainly in African-American subjects. Such a situation is exceedingly rare in Caucasian patients with non-malignant hypertension. The direct effect of pressure is well evidenced experimentally in the 2 kidneys-one clip Goldblatt model: only in the unclipped kidney which is exposed to high blood pressure, vascular lesions develop in interlobular arteries and afferent arterioles, followed by glomerular sclerosis. The pressureinduced glomerular damage is limited by an autoregulation based on vasoconstriction of the afferent arteriole. The efficiency of this autoregulation is largely under genetic influence. A deficient autoregulation with vasodilated afferent arterioles leads to more early and severe glomerular damage. Conversely, afferent arteriolar vasodilatation, with glomerular hyperfiltration, may precede any increase in blood pressure. This occurs mainly when sodium excretion is limited, due to any congenital functional defect, or a reduced number of nephrons. Hypertension occurs secondarily, and appears as the hemodynamic counterpart necessary to maintain the sodium balance. In this case, the same primary renal abnormality causes both hypertension and glomerulosclerosis. This is believed to be a frequent cause of hypertension-associated glomerulosclerosis. Whatever the sequence of events, reducing blood pressure is the best way to limit kidney damage. Antihypertensive drugs have, however some actions on renal circulation independent of blood pressure. Calcium channel blockers blunt the autoregulation of afferent arterioles. On the contrary, drugs which inhibit the renin angiotensin system reduce glomerular capillary pressure, and have a beneficial effect on the progression of renal failure.
Keywords: Renal function